Hepcidin and Ferritin Predict Microbial Etiology in Community-Acquired Pneumonia. (18th February 2021) - Oppen, Kjersti; Ueland, Thor; Siljan, William Ward; Skadberg, Øyvind; Brede, Cato; Lauritzen, Trine; Aukrust, Pål; Steinsvik, Trude; Husebye, Einar; Michelsen, Annika E; Holter, Jan Cato; Heggelund, Lars
Abstract: Background: Iron is crucial for survival and growth of microbes. Consequently, limiting iron availability is a human antimicrobial defense mechanism. We explored iron and iron-related proteins as potential biomarkers in community-acquired pneumonia and hypothesized that infection-induced changes in these potential biomarkers differ between groups of pathogens and could predict microbial etiology. Methods: Blood samples from a prospective cohort of 267 patients with community-acquired pneumonia were analyzed for hepcidin, ferritin, iron, transferrin, and soluble transferrin receptor at admission, clinical stabilization, and a 6-week follow-up. A total of 111 patients with an established microbiological diagnosis confined to 1 microbial group (atypical bacterial, typical bacterial, or viral) were included in predictive analyses. Results: High admission levels of ferritin predicted atypical bacterial versus typical bacterial etiology (odds ratio [OR], 2.26; 95% confidence interval [CI], 1.18–4.32; P = .014). Furthermore, hepcidin and ferritin predicted atypical bacterial versus viral etiology (hepcidin: OR = 3.12, 95% CI = 1.34–7.28, P = .008; ferritin: OR = 2.38, 95% CI = 1.28–4.45, P = .006). The findings were independent of C-reactive protein and procalcitonin. Conclusions: Hepcidin and ferritin are potential biomarkers of microbial etiology in community-acquired pneumonia. Abstract : In this prospective cohort of community-acquired pneumonia patients, levels of the iron-related proteins hepcidin and ferritin were higher in atypical bacterial etiology, especially compared with viral etiology. Hepcidin and ferritin merge as potential biomarkers of microbial etiology in community-acquired pneumonia.